THE IMPLEMENTATION OF MATERIAL CRIMINAL LAW TOWARD THE CRIME OF TRAFFICKING IN PERSONS - Warsifah, Warsifah; Mangatur , Julius (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
The unbalanced and unequal economic growth in society often creates social and social jealousy in the community. On the one hand, there is a group of people who have sufficient capacity economically, but on the other hand there is a group of people who have no economic capacity in their lives, so that the latter group is often a social problem that even commits the crime of theft, for example. The criminal act of theft according to the Criminal Code, there is an element of